Regulation of Exopolysaccharide Production by ProE, a Cyclic-Di-GMP Phosphodiesterase in Pseudomonas aeruginosa PAO1 - Feng, Qishun; Ahator, Stephen Dela; Zhou, Tian; Liu, Zhiqing; Lin, Qiqi; Liu, Yang; Huang, Jiahui; Zhou, Jianuan; Zhang, Lian-Hui (Frontiers in Microbiology, 2020)
The ubiquitous second messenger c-di-GMP is involved in regulation of multiple biological functions including the important extracellular matrix exopolysaccharides (EPS). But how c-di-GMP metabolic proteins influence EPS and their enzymatic properties are not fully understand. Here we showed that deletion of proE, which encodes a protein with GGDEF-EAL hybrid domains, significantly increased the transcriptional expression of the genes encoding EPS production in P. aeruginosa PAO1 and changed the bacterial colony morphology. Our data showed that ProE is a very active phosphodiesterase (PDE), with a high efficiency in degradation of c-di-GMP. Interestingly, native PAGE analysis showed that ProE appears to exist as a tetramer, which is quite unusual compared with other enzymes. In addition, the optimal activity of ProE was found in the presence of Co 2+ , unlike other PDEs that commonly rely on Mg 2+ or Mn 2+ for best performance. Furthermore, we identified three widely conserved novel residues that are critical for the function of ProE through site-directed 2 mutagenesis. Subsequent study showed that ProE, together with other three key PDEs, i.e., RbdA, BifA and DipA regulate the EPS production in P. aeruginosa PAO1.Moreover, by using the GFP-fusion approach, we observed that these four EPS associated-PDEs showed a polar localization pattern in general. Taken together, our data unveal the molecular mechanisms of ProE in regulation of EPS production, and provide a new insight on its enzymatic properties in degradation of c-di-GMP.